Three new species of Nazeris Fauvel in Xizang, China (Coleoptera, Staphylinidae, Paederinae) - Hu, Jia-Yao; Pan, Zhao-Hui; Li, Li-Zhen (Zootaxa, 2016)
The paederine genus Nazeris Fauvel, 1873 previously included 241 described species and seven subspecies (Assing, 2016). As many as 49 species have been recorded from the Himalaya (Assing, 2014). In China, Yunnan has the greatest diversity of Nazeris (45 species). Xizang is the second largest province of China, and adjacent to Yunnan and the Himalaya. But only two Nazeris species have been described from this area: N. motuensis Hu, Li & Zhao, 2008 and N. tangi Hu, Li & Zhao, 2008. Both of them were found in eastern Xizang. Three additional species in the insect collection of the Shanghai Normal University are described in this paper.